Changes and interactions of milk components over one year by months - Darbaz, Tahire; Ulusoy, Beyza; Darbaz, Isfendiyar; Zabitler Tepik, Feride; Hecer, Canan; Aslan, Selim (Revista Científica de la Facultad de Ciencias Veterinarias, 2024)
This study was carried out by collecting tank milk samples every month, from a total of 240 farms producing cold chain milk for one year. Somatic cell count (SCC), total bacterial count (TBC), some nutritional elements (lactose, protein, casein, fat) and some physicochemical parameters (dry matter, fat–free dry matter, freezing point, density, free fatty acids, Soxhlet Henkel acidity degree) and citric acid were analyzed. According to the results; TBC were at the highest level in March (M), April (A) and June (J) (835.07 x103; 940.25 × 103 and 1007.30 × 103 cfu·mL–1), whereas between July (Ju) and December (De), TBC (446.09 × 103 and 795.15 × 103 cfu·mL–1) were significantly lower (P<0.001). The highest SCC were found in M, A and May (Ma), whereas the lowest SCC were found between September (S) and De. Between S and De, when SCC decreased, (varied between 236.13 × 103 cells·mL–1 and 284.43 × 103 cells·mL–1; P<0.05). Lactose values were found to be significantly higher in spring and summer compared to other months. A significant decrease was determined in protein values in the summer months compared to November (N) and De (P<0.05; P<0.01). It was also revealed that casein values were higher in the summer months Ma–August (Au) compared to the other lower months (P<0.01). For physico–chemical parameters, it was determined that non–fat solids and freezing point (FP) values decreased significantly during the summer months (P<0.01; P<0.001). The results obtained show that the parameters in question are seasonally affected, but these parameters change depending on the changes in both TBC and SCC values (high level of positive or negative correlation).